Pentingnya Peran Orang Tua dalam Pendidikan Anak di Wamena, Papua Pegunungan - Rahayu, Nurita Angesti; Huby, Rahel; Manuel, Gerson; Heluka, Yosina (Universitas Pahlawan Tuanku Tambusai, 2025)
The increasingly complex challenges of education require awareness, active participation, and contribution from parents in educating children. Efforts made to increase understanding of the crucial role of parents in educating children through seminar activities. The seminar was held in the yard of St. Petrus Holima Wamena Church, Jayawijaya Papua Pegunungan. The main target of this seminar was parents who live in Holima. The strategies used were material presentation, discussion, feedback and follow-up. Data collection for Community Service (PkM) was through FGD (Focus Group Discussion) and documentation. The results of the seminar activities have provided a good understanding for parents regarding the basic needs of children that must be met and the important role of parents. This seminar provides good awareness for parents, that education is a close partnership between parents and educational institutions, not just the responsibility of the school.